Hypothesis and theory: Do trees “release the tension” in rainwater? Surface tension reduction in throughfall and stemflow from urban trees - Noren, Benjamin J.; Lewis, Nicholas R.; Tonello, Kelly Cristina; Ilek, Anna; Van Stan, John T. (Frontiers in Forests and Global Change, 2023)
Knowledge of the processes and impacts associated with the canopy’s partitioning of rainfall into stemflow (water that drains to the base of tree stems) and throughfall (water that drips through gaps and from canopy surfaces) has expanded in recent years. However, the effect of canopy interactions on the fundamental physical properties of rainwater as it travels through the canopy to the soil, particularly surface tension, remains understudied. To discuss specific hypotheses within this context and their relevance to ecohydrological theory, the surface tension of rainwater samples was examined directly. Over a period of 9 months, open rainwater, throughfall and stemflow samples were collected during 20 storms from 12 study trees located in Secrest Arboretum (about 2.5 km outside Wooster, Ohio). Study trees were selected to highlight a range of canopy characteristics, with each tree being from a unique deciduous species. Surface tension was measured using pendant drop goniometry, and measurements were analyzed for variation across study trees and correlation with event air temperature and rain intensity. In general, surface tension was reduced in throughfall and stemflow compared to measurements made for event rainwater, with median surface tension changes of -0.446 mN m-1 and -0.595 mN m-1 for throughfall and stemflow respectively. The extent of this reduction varied among study trees (with changes as great as -6.5 to -5.5 mN m-1), and storm event characteristics were directly and indirectly correlated with surface tension changes in select cases. Hypothetically, a number of mechanisms may account for the observed reduction (and variation in this reduction) in surface tension, including differences in tree surface properties, canopy microenvironments, and microbiomes, and each warrant further research. Testing these hypotheses may advance broader ecohydrological theory as surface tension changes will influence wetting, absorption, and solute exchange processes within the canopy which, in turn, may affect related surface processes.